ANALISIS KOMODITAS UNGGULAN TANAMAN PANGAN DAN HORTIKULTURA DI KABUPATEN MEMPAWAH - IRMAYADI, ADE; YURISINTHAE, ERLINDA; SUYATNO, ADI (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2016)
Mempawah Regency Government has a mission to improving the economy that oriented to the community. The goal is to develop the economy through food security (agriculture commodity crops, horticulture, livestock, fisheries and biodiversity) and reinforced by forests management and plantations to improve the welfare of farmers. Mempawah regency is one of the regencys that the economic life of the people still depend on agribusiness system, particularly the agricultural sector. Based on the (Gross Regional Domestic Product) GRDP value of Mempawah Regencys years 2008 to 2012 the agricultural sector, especially the food crops subsector has the highest contribution to Mempawah Regency’s GRDP compared to other subsectors. The goal of this study is to analyze which subsector that became the basis of agricultural sector in the Mempawah Regency and the leading commodity of food crops and horticulture. This study uses three analysis tools i.e Dynamic Location Quotient Analysis to analyze what is the basis of the agricultural sector in the Mempawah Regency. Shift-Share Analysis and Growth Ratio Model Analysis to analyze any commodity which is the leading commodities of food crops and horticulture. The results from this study is, subsectors which are the basis of the agricultural sector in the Mempawah Regency is the food crops, forestry, and fishery subsector. The leading commodity in the Mempawah Regency of food crops are rice, the leading commodities of vegetables are cucumbers and kangkung, and the leading commodity of fruits are bananas.Keywords : Basis, Leading Sector, Food Crops Subsector and Horticulture